Resíduo seco da industrialização da acerola na alimentação de suínos na fase inicial - Leal, Isabela Ferreira (2018)
The objective of this study was to evaluate the nutritional value of dry residue of acerola industrialization (DRAI) for piglets in the starter phase and its effects on the growth performance, nitrogen balance and blood urea (BU). In the Exp. I, a digestibility trial was carried out using 24 entire male piglets, with an initial weight of 21.07±3.07 kg, that were distributed in a randomized complete block design (RCBD), consisting of two treatments, 12 replications and one swine per experimental unit. Treatments consisted of a reference feed (RF: 0% DRAI) and a test feed with replacement of 20% of the DRAI in the RF. Total feces and urine collection were performed to determine DRAI composition and nutrient digestibility. In the Exp. II a nitrogen balance assay (NB)was carried out using 24 entire male piglets, with an average initial weight of 20.78±1.84 kg, that were distributed in a RCBD consisting of four treatments, six replicates and one animal per experimental unit. Treatments consisted of four feeds with increasing inclusion levels (0, 4, 8 and 12%) of DRAI. Total collection of feces and urine was performed to determine the amount of nitrogen ingested, excreted and retained. The Exp. III, was a growth performance trial using 120 crossbreed piglets (60 entire males and 60 females), with an average initial weight of 13.85±1.49 kg and final weight of 25.08±1.06 kg, that were distributed in a RCBD with six replicates and four animals per experimental unit. Treatments consisted of five increasing inclusion levels (0, 3, 6, 9 and 12%) of DRAI. To determine the best level of DRAI inclusion for piglets in starter phase, was evaluated the final body weight (FBW), daily feed intake (DFI), daily weight gain (DWG), feed conversion (FC) and BU. The bromatological-energy composition of the DRAI was: 86.12% dry matter (DM), 8.03% crude protein (CP), 4.553 kcal.kg-1 gross energy (GE), 55.09% neutral detergent fiber (NDF) and 22.26% acid detergent fiber (ADF). The results showed digestibility coefficients of 39.04 and 28.21% for CP and GE, respectively. For the variables analyzed in the NB, no differences (P≥0.05) were found among treatments. For growth performance, it was observed effect of DRAI levels on FBW, DWG and DFI, however there was no effect of DRAI levels on the FC and BU. The estimated values of DRAI level that provided the maximum estimate of FBW, DWG and DFI were 2.93, 3.05% and 4.27%, which resulted in values of 25.70 kg for FBW, 0.636 kg of DWG and 1.15 kg of DFI. The best level of DRAI inclusion in piglets feeding in the starter phase was 2.93 to 4.27%.